1994
DOI: 10.1080/03014223.1994.9518013
|View full text |Cite
|
Sign up to set email alerts
|

Habitat distribution and predation on a western population of terrestrialLeiopelma(Anura: Leiopelmatidae) in the northern King Country, New Zealand

Abstract: A new population of terrestrial Leiopel-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 1 publication
2
67
0
Order By: Relevance
“…Morphologically, L. pakeka differs from L. hamiltoni in its more variable dorsal colour, darker individuals prevalent on Maud Island evidently being absent from Stephens Island, although fewer frogs were examined there (Bell 1978a(Bell , 1982a(Bell , 1985b. Just as some L. pakeka specimens can show small amounts of green colouring (Barwick 1961, Bell 1978a, Bell 1995, so can some L. hamiltoni from Stephens Island, although not as conspicuously green as some L. archeyi (Bell 1978a, Thurley & Bell 1994Thurley 1996). L. pakeka reaches a slightly greater body size than L. hamiltoni (maximum snout-vent lengths 49 mm and 46 mm respectively - Fig.…”
Section: Differentiation From Other Taxa Allozyme Variation and Populmentioning
confidence: 99%
See 2 more Smart Citations
“…Morphologically, L. pakeka differs from L. hamiltoni in its more variable dorsal colour, darker individuals prevalent on Maud Island evidently being absent from Stephens Island, although fewer frogs were examined there (Bell 1978a(Bell , 1982a(Bell , 1985b. Just as some L. pakeka specimens can show small amounts of green colouring (Barwick 1961, Bell 1978a, Bell 1995, so can some L. hamiltoni from Stephens Island, although not as conspicuously green as some L. archeyi (Bell 1978a, Thurley & Bell 1994Thurley 1996). L. pakeka reaches a slightly greater body size than L. hamiltoni (maximum snout-vent lengths 49 mm and 46 mm respectively - Fig.…”
Section: Differentiation From Other Taxa Allozyme Variation and Populmentioning
confidence: 99%
“…archeyi is smaller than L. pakeka (maximum snout-vent length 38 mm) and has more varied colouring including green, pink and orange-brown on the dorsal surfaces (Bell 1978a(Bell ,1993Thurley & Bell 1994;Thurley 1996). L. hochstetteri has a more robust form, with shorter fingers and toes, and distinctive toe webbing.…”
Section: Differentiation From Other Taxa Allozyme Variation and Populmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats (Rattus spp.) are considered a primary factor contributing to the extinction of New Zealand's herpetofauna (Worthy 1987;Bell 1994;Thurley & Bell 1994;Towns & Daugherty 1994). At present, only ship rats (Rattus rattus) are abundant on Maungatautari, replacing the kiore (R. exulans) and the Norway rats (R. norvegicus) that attained great numbers in the past.…”
Section: Factors Affecting Observed Hochstetter's Frog Abundancementioning
confidence: 99%
“…During a study of Leiopelma archeyi in Whareorino, Thurley and Bell (1994) decided to investigate the stomach contents of L. aurea found at the same locality. To their surprise they discovered a pair of hind legs of L. archeyi and concluded that in this population the bell frogs have the potential to cause a lot of damage.…”
Section: Bishop Bell Frog Populations In New Zealandmentioning
confidence: 99%